2014
DOI: 10.1021/ja5037308
|View full text |Cite
|
Sign up to set email alerts
|

Mixing, Diffusion, and Percolation in Binary Supported Membranes Containing Mixtures of Lipids and Amphiphilic Block Copolymers

Abstract: Substrate-mediated fusion of small polymersomes, derived from mixtures of lipids and amphiphilic block copolymers, produces hybrid, supported planar bilayers at hydrophilic surfaces, monolayers at hydrophobic surfaces, and binary monolayer/bilayer patterns at amphiphilic surfaces, directly responding to local measures of (and variations in) surface free energy. Despite the large thickness mismatch in their hydrophobic cores, the hybrid membranes do not exhibit microscopic phase separation, reflecting irreversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
68
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 33 publications
4
68
4
Order By: Relevance
“…33 Therefore, these synthetic BCP membranes mimic natural lipid bilayers with respect to the membrane fluidity and do not have to be blended with fast diffusing lipids in order to increase their fluidity. 34 Furthermore, the functional incorporation of a small biopore (gramicidin) with height in the range of the present MPs in BCP giant unilamellar vesicles (BCP-GUVs), similar to the GUVs used in this study, was reported very recently. 21 Gramicidin was successfully inserted in synthetic membranes up to 13 nm thick, whereas thicker membranes (for example 16.2 nm) prevented a functional biopore insertion.…”
supporting
confidence: 64%
“…33 Therefore, these synthetic BCP membranes mimic natural lipid bilayers with respect to the membrane fluidity and do not have to be blended with fast diffusing lipids in order to increase their fluidity. 34 Furthermore, the functional incorporation of a small biopore (gramicidin) with height in the range of the present MPs in BCP giant unilamellar vesicles (BCP-GUVs), similar to the GUVs used in this study, was reported very recently. 21 Gramicidin was successfully inserted in synthetic membranes up to 13 nm thick, whereas thicker membranes (for example 16.2 nm) prevented a functional biopore insertion.…”
supporting
confidence: 64%
“…Generating supported polymer bilayers and supported hybrid lipid/polymer bilayers (SHBs) offers another practical approach towards robust and stable biomimetic platforms. Indeed, there is a growing interest in understanding and exploiting the formation of SHB films in the past few years [22][23][24][25][26][27], including the use of amphiphilic polymers to complement the library of conventional lipids. Such hybrid materials have recently been highlighted as an important development toward biomimetic interfaces [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, relatively little information is available about the structure, chemical nature, and molar mass of copolymers that could mix ideally with phospholipids. Most commonly, poly(butadiene) [3][4][5][6][7][8][9][10][11][12] and poly(dimethylsiloxane) [13][14][15][16][17][18][19][20] have been used as hydrophobic block, while studies with poly(isobutene) [21][22][23], poly(caprolactone) [24,25], poly(isoprene) [26], and poly(laurylacrylate) [27] have also been reported. Poly(ethylene oxide) is by far the most used hydrophilic block, although few studies report the use of hydrophilic thermo-responsive blocks such as poly(2-isopropyl-2-oxazoline) [28] and poly(ethylene glycoldiacrylate) [27].…”
Section: Introductionmentioning
confidence: 99%